Noncontingent reinforcement without extinction plus differential reinforcement of alternative behavior during treatment of problem behavior. Issue 3 (17th May 2017) - Fritz, Jennifer N.; Jackson, Lynsey M.; Stiefler, Nicole A.; Wimberly, Barbara S.; Richardson, Amy R.
Abstract : The effects of noncontingent reinforcement (NCR) without extinction during treatment of problem behavior maintained by social positive reinforcement were evaluated for five individuals diagnosed with autism spectrum disorder. A continuous NCR schedule was gradually thinned to a fixed‐time 5‐min schedule. If problem behavior increased during NCR schedule thinning, a continuous NCR schedule was reinstated and NCR schedule thinning was repeated with differential reinforcement of alternative behavior (DRA) included. Results showed an immediate decrease in all participants' problem behavior during continuous NCR, and problem behavior maintained at low levels during NCR schedule thinning for three participants. Problem behavior increased and maintained at higher rates during NCR schedule thinning for two other participants; however, the addition of DRA to the intervention resulted in decreased problem behavior and increased mands.